DEEP SEABED MINING AND PRECAUTIONARY PAUSE: POSSIBILITY AND LEGAL CHALLENGES - Ariningtyas, Agnes (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
Critical minerals that are greatly needed for green technology could be found in potentially promising quantities on the seafloor. Nevertheless, there are long-term environmental effects associated with recovering such nature of a resources. This research argues based on international law of the sea which applies normative-legal research method using statutory and conceptual approaches. The main findings of this research reveal that the proponents argue that extracting minerals from the deep sea could be beneficial for the humankind, particularly its reliance on electric vehicles, batteries, and zero-carbon technologies. However, many nations are pushing for a ban or delay on seabed mining due to a lack of international law and knowledge of the full environmental effects. For example, direct harm to marine life, long-term species and ecosystem disruption, economic and social risks, and potential climate impacts that would most likely be permanent It is unclear if the International Seabed Authority (ISA) will approve such a ban, but some scientists believe mining will start soon. Therefore, to continue the exploration of deep seabed mining (DSM), regulations should be drafted in full and transparent including the precautionary approach needs to be implemented to minimize the potential destructive impacts due to the DSM activities.